Seizure commonly associated with Neurocysticercosis are not linked with pork meat diet. A retrospective analysis - Khanal, Nisha; Shrestha, Reena (Asian Journal of Medical Sciences, 2019)
Background: Neurocysticercosis (NCC) is a neglected tropical disease and common cause epilepsy in developing countries. Aims and Objectives:The purpose of the study was to determine the prevalence of NCC and factor associated with the cause of NCC in Nepalese patients. Material and Methods: All patient with complain of seizure admitted to the College of Medical Sciences, and Teaching Hospital (COMS-TH), Nepal for a period of 2016 were included in the study. All age group patients between 10-80 years old with confirmed diagnosed of NCC were considered for the retrospective analysis. The proportion distribution of NCC was categorized based on the etiology of seizures, demographic profile (gender and age) and dietary habit of patients. Results: Among 142 patients with seizure, 54(38%) were computerized tomography (CT) scan confirmed NCC cases in which 29 (53.7) were male, and 25 (46.3%) were female. Almost 44 (81.5%) patients with NCC were below the age of 50 years, and high prevalence (31.5%) was observed at the age of 10-20 years old patients. All patients depend on the agricultural background, in which 35 (65%) were farmer and 19 (35%) with an agricultural background. Most of the patients lacked good hygienic habits. Additionally, 10 (18.5%) patients with NCC were vegetarian, 44 (81.5%) were non-vegetarian. Among non-vegetarian, only 2 (3.7%) were pork eaters. Most of the patients had poor hygienic habits and eating raw vegetables. All patients were managed with the single antiepileptic drug but, Albendazole plus steroid therapy was added in patients with active lesion observed in CT scan. Conclusions:This study showed a high prevalence of NCC and a common cause of the new onset of seizures in the patient of COMS-TH, Nepal. Also, our data showed that NCC is not associated with pork eaters because NCC was observed more number in vegetarian compared to patients who consume pork meat diet.